Living arrangements and quality of life among older adults in China: does social cohesion matter?. (1st December 2020) - Huang, Xiaoning; Liu, Jinyu; Bo, Ai
Abstract: Objectives: This study investigated how living arrangements are related to the well-being of Chinese older adults and the role of social cohesion in this relationship. Methods: This study used the China data from the WHO's Study on Global AGEing and Adult Health. The analytic sample featured 5, 600 Chinese adults aged 60 or older. The study conceptualized two sets of models: social cohesion as mediators and as moderators in the relationship of living arrangements and quality of life. Results: Results from structural equation modelling analyses show that Chinese older adults who lived with adult children had lower quality of life scores compared with those who did not live with adult children; the negative relationship was partially mediated through decreased social cohesion. The study also found social cohesion may buffer the negative influence of not living with a spouse compared with those who did. Conclusion: This study sheds light on the mediating and moderating effects of social cohesion on the relationship between living arrangement and quality of life among older adults in China. The findings indicate the necessity of promoting social connectedness and neighborhood cohesion for older Chinese, especially those who live with their adult children.